HAMBATAN KONSELING MULTIKULTURAL: BIAS BUDAYA DALAM PROSES KONSELING - Winda Melinda (Universitas Pendidikan Indonesia, 2023)
Multicultural counselling is a process of cultural encounter between counsellors and counselees from different cultural backgrounds. Multicultural counselling finds obstacles in it because clients bring different world perspectives that are shaped by various cultural experiences, such as a different race from the counsellor so that there are obstacles in the multicultural process in the form of cultural bias. Cultural bias can affect the interaction between counsellors and clients with different cultural backgrounds, hindering the achievement of counselling goals. To overcome these barriers, it is important for counsellors to continue to develop cultural awareness, enhance cultural skills, and commit to understanding and appreciating cultural differences in the counselling context. An approach that is responsive to cultural diversity will help create an inclusive and effective counselling environment for all individuals. This article encourages counsellors to adopt a more inclusive approach in their counselling practice. By doing so, the counselling process can be more effective, responsive to the needs of diverse clients, and help realise clients' goals of optimal recovery and personal growth.